Muslim Tourists' Perception of Halal Tourism: A Qualitative Study based on the Theory of Planned Behavior (TPB) - Afif, Nur Choirul; Lutfiyati, Riya Zulfa (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
Halal tourism has grown rapidly as one of the most important segments in the global tourism industry. However, understanding of the factors that influence the behavior of Muslim tourists in choosing halal tourism destinations is still very limited, This research aims to explore Muslim tourists' perception of halal tourism using the framework of the Theory of Planned Behavior (TPB), which includes attitudes, subjective norms and perceived behavioral control. This study uses a qualitative approach with an in- depth interview method. The sample of this study consisted of 30 Muslim tourists who had visited halal tourism destinations. The data were analyzed thematically to identify patterns and themes that emerged from the respondents' narratives regarding their perception of halal tourism and factors influencing the decision to visit. The results of the study show that positive attitudes towards halal tourism, subjective norms from family and friends, and perceived behavioral control in terms of the availability of information and facilities in accordance with Sharia are key factors that affect the intention of Muslim tourists to visit halal tourism destinations. In addition, this study also found that the trust and reputation of destinations and previous experiences also play an important role in shaping the perception and intentions of Muslim tourists. This study provides in-depth insights into how Muslim tourists perceive halal tourism and the factors that influence tourists' decisions based on the framework of the Theory of Planned Behavior (TPB). The findings of this study can be used by tourism developers and marketers to design more effective strategies in targeting and serving the Muslim tourist market, as well as improving the quality of services and facilities according to their preferred needs